The Coffee Village and Republik Kopi: The Production–Consumption Nexus in Bondowoso’s Identity Construction - Harnadi, Dodik; Prasetro, Hery; Rosa, Dien Vidia (Universitas Djuanda, 2025)
This article addresses a significant gap in studies on regional identity, which often emphasize consumption while neglecting the role of production in shaping local identity. In response, this study investigates how local identity in Bondowoso is co-constructed through coffee production and consumption, particularly through the Kampung Kopi Pelita initiative. The research examines how historical legacies, state interventions, and everyday entrepreneurial practices intersect in making Bondowoso's Republik Kopi identity. This study used a qualitative Grounded Theory approach to examine the co-construction of local identity in Bondowoso. Data were collected through 25 semi-structured interviews with key actors in Kampung Kopi Pelita, including coffee entrepreneurs, Pokdarwis members, and community leaders. To complement the interviews, an FGD with 20 participants was held. These methods enabled a rich analysis of identity formation's symbolic, economic, and political aspects, with data reaching thematic saturation. The findings challenge dominant consumption-based perspectives by Arslan & Coskun, which underplay the productive agency of local actors. Instead, the study develops a model of identity co-creation where producers and consumers mutually shape symbolic meanings and regional imaginaries. Theoretically, it enriches Giddens' concept of reflexive identity by embedding it in local economic practices. Practically, this research provides insight into how rural branding initiatives can be more inclusive by involving grassroots entrepreneurial actors. In conclusion, Kampung Kopi Pelita emerges not merely as a commercial space but as a cultural arena where local identity is contested, negotiated, and collectively imagined.